2013
DOI: 10.1530/rep-13-0017
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species production and redox state in parthenogenetic and sperm-mediated bovine oocyte activation

Abstract: The knowledge concerning redox and reactive oxygen species (ROS)-mediated regulation of early embryo development is scarce and remains controversial. The aim of this work was to determine ROS production and redox state during early in vitro embryo development in sperm-mediated and parthenogenetic activation of bovine oocytes. Sperm-mediated oocyte activation was carried out in IVF-modified synthetic oviductal fluid (mSOF) with frozen-thawed semen. Parthenogenetic activation was performed in TALP plus ionomycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 45 publications
(27 reference statements)
2
17
0
Order By: Relevance
“…However, a significant number of patients with normal sperm parameters still undergo difficulty in achieving successful pregnancy [ 13 ]. Several new diagnostic biomarkers for semen quality have been investigated recently including PLCζ, oxidative stress and DFI [ 14 ]. Here, we first demonstrated that sperm PLCζ immunoreactivity has a negative correlation with a oxidation marker, 8-OHdG.…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant number of patients with normal sperm parameters still undergo difficulty in achieving successful pregnancy [ 13 ]. Several new diagnostic biomarkers for semen quality have been investigated recently including PLCζ, oxidative stress and DFI [ 14 ]. Here, we first demonstrated that sperm PLCζ immunoreactivity has a negative correlation with a oxidation marker, 8-OHdG.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Hydrogen peroxide (H 2 O 2 ) is an important ROS in reproductive health, and its detection is vital for monitoring embryo health and the diagnosis of male infertility. H 2 O 2 is typically detected in cells using a compound (fluorophore) that fluoresces on its reaction with ROS.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that certain amount of ROS is essential for the successful fertilization process [ 35 ]. In case of sperm-activated oocytes, ROS peaks are associated with fertilization events such as sperm penetration and sperm head decondensation [ 36 ]. However, our data suggest that increase in ROS level is independent of sperm deposition but may be related to mechanical stress induced during mock injection process since both in vivo matured and IVM oocytes subjected to mock injection had significantly higher level of ROS compared to standard and ICSI controls.…”
Section: Discussionmentioning
confidence: 99%